Why we need to “grasp” our surroundings: object affordance and prehension in architecture - Salingaros, Nikos (Journal of Architecture and Urbanism, 2017)
This paper argues for a basic need for graspable “handles” to be physically present, or merely suggested in our immediate environment. Yet two of the most characteristic elements of industrial-modernist architecture, plate-glass curtain walls and minimalist surfaces, fail to match this aspect of our body’s biology. The absence of graspable components from the formal architecture of the 20th Century leads to psychological disconnection on the part of the user, and could possibly be a cause for stress and anxiety. Physical built elements and designs suggestive of grasping arise in traditional and vernacular methods of construction as ubiquitous moldings, ornament, and trim in response to both human psychology and tectonics.